STUDI KELAYAKAN FINANSIAL PENAMBAHAN KAPAL LINTASAN LEMBAR – PADANGBAI PADA PT XXX - Syafiuddin Syafiuddin; Taufik Fajar Nugroho (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Increasing the number of ships that operate at a certain track is one way to support overall company’s performance. With the result business management should consider the balance of transportation service demand. Since the ship procurement was delayed and the long-distance ferry services adding up for Lombok, the feasibility profile need to be reconsidered. The case that one ship will be rejuvenated while the other ship already reaches the operational life. Besides, the increased demand on Lembar-Padangbai track is an opportunity to develop the company. Using 7 years of production historical data, technical data of 77.72 m of overall length roro vessel, the consumption cost, operational parameters, and also investment parameters, and 65.51 on load factors (LF), the study shows optimistic financial feasibility results. IRR value 15.97% and this value is higher than the Weighted average cost of capital (WACC) 9.83% and payback-period is 12 years for 20 years of operational life. Sensitivity analysis shows that the higher self-financing percentage gives a better financial feasibility value.